Social Media as a New Space for Moderation Politics and Religious Expression - Meisya Nur Dwi (Social Impact Journal, 2025)
Social media has now become a significant space in the formation of religious discourse and the dissemination of moderate values in Indonesia. This study aims to understand how social media is used as a political space for moderation as well as a means of religious expression by various digital religious actors. Using a qualitative approach, this study combines content analysis and digital discourse studies on various religious content spread across platforms such as YouTube, TikTok, Instagram, Twitter, and Facebook. Data were obtained through a netnography-based digital observation method, including preaching videos, uploads by religious figures, and public discussions in comments or live streaming. The findings show that social media has become an effective channel in conveying moderate, tolerant, and inclusive religious messages, especially through creative communication strategies such as the edutainment approach and redistribution of preaching content in short formats. However, this potential is also accompanied by serious challenges, including digital polarization due to platform algorithms and resistance from conservative groups who reject moderate narratives. Thus, social media can play a role as a strategic tool in supporting Religious Moderation in Indonesia, as long as it is accompanied by cross-actor collaboration and strengthening of the community's digital religious literacy.